2021
DOI: 10.31234/osf.io/bm945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Valence, form, and content of self-talk predict sport type and level of performance

Abstract: In this paper, we aimed to test whether we could predict sport type (badminton or running) and marathon proficiency from the valence, form, and content of the athletes’ self-reported inner speech. Additionally, we wanted to assess the difference between self-talk during high intensity and low intensity exercise. The present study corroborated existing research – we were able to predict both sport type in Study 1 and intensity level as well as marathon proficiency in Study 2 from questionnaire data using machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…The interaction we found between self-talk and pressure on both tasks met our expectation and echoed prior research showing that athletes under pressure tend to use self-talk to enhance their sports performance (Boudreault et al, 2018; Nedergaard et al, 2021). According to Beilock et al (2002; 2007), being under pressure distracts the performer’s attention from the required focus and impairs performance.…”
Section: Discussionsupporting
confidence: 89%
“…The interaction we found between self-talk and pressure on both tasks met our expectation and echoed prior research showing that athletes under pressure tend to use self-talk to enhance their sports performance (Boudreault et al, 2018; Nedergaard et al, 2021). According to Beilock et al (2002; 2007), being under pressure distracts the performer’s attention from the required focus and impairs performance.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, badminton players have little time to decide where and what kind of shot they should play thus cause great pressure. Recent research compared self-talk across sport types and exploring how skill-level is related to performance found that, badminton players' self-talk was more characterized by self-regulated anxiety [15]. In the present study, we aimed to test whether self-talk could be effective in overcoming choking, and whether decisive self-talk will be more effective than other types of self-talk under such high pressure in the real competition situations.…”
Section: Associative Processesmentioning
confidence: 94%